"i hair": A prognostic marker in alopecia areata & trichotillomania - Subrata Malakar; Purva Ranjit Mehta (Wolters Kluwer Medknow Publications, 2017)
Trichoscopy as an investigative tool is revolutionizing the diagnosis of hair disorders. The use of a trichoscope has unveiled a plethora of signs which not only helps in decoding the underlying tricoscopic condition but also acts as prognostic markers. Herein, we present a new trichoscopic sign, "i hair" in alopecia areata and trichotillomania. "i hair" are short hairs with an accentuated distal end. There may be a thin hypopigmented shaft just beneath the darker distal end, thus making them resemble the alphabet "i."